Nonlinear model-based track guidance of user-defined points at the vehicle front. (August 2015) - Hahn, Stefan; Zindler, Klaus; Jumar, Ulrich
Abstract: Preventive pedestrian protection systems are validated by means of fully automated driving tests reproducing safety-critical traffic situations on a proving ground. In order to assess these preventive safety systems, a precise and reproducible collision of a pedestrian dummy with a specific point at the vehicle front, e.g., the left corner of the vehicle, must be ensured. Hence, a track guidance of this specific point is required. Beyond the state of the art a new nonlinear model describing the lateral deviation of any point at the vehicle front to a predefined path is proposed in this paper. Based on this model the method of input–output linearization is used to design a flexible lateral guidance system for an easy application in different vehicles. Furthermore, the closed-loop stability is proven and experimental results are presented. Abstract : Highlights: New model describing the dynamics of a large variety of points at the vehicle body. Track guidance of such specific points by applying input–output linearization. Proof of closed-loop stability. Experimental results of the developed lateral vehicle guidance system. Precise track guidance with maximal lateral deviations of less than 3 cm.